Molecular characterization of colorectal adenomas reveals POFUT1 as a candidate driver of tumor progression. Issue 7 (30th August 2019) - Komor, Malgorzata A.; de Wit, Meike; van den Berg, Jose; Martens de Kemp, Sanne R.; Delis‐van Diemen, Pien M.; Bolijn, Anne S.; Tijssen, Marianne; Schelfhorst, Tim; Piersma, Sander R.; Chiasserini, Davide; Sanders, Joyce; Rausch, Christian; et al.
Abstract : Removal of colorectal adenomas is an effective strategy to reduce colorectal cancer (CRC) mortality rates. However, as only a minority of adenomas progress to cancer, such strategies may lead to overtreatment. The present study aimed to characterize adenomas by in‐depth molecular profiling, to obtain insights into altered biology associated with the colorectal adenoma‐to‐carcinoma progression. We obtained low‐coverage whole genome sequencing, RNA sequencing and tandem mass spectrometry data for 30 CRCs, 30 adenomas and 18 normal adjacent colon samples. These data were used for DNA copy number aberrations profiling, differential expression, gene set enrichment and gene‐dosage effect analysis. Protein expression was independently validated by immunohistochemistry on tissue microarrays and in patient‐derived colorectal adenoma organoids. Stroma percentage was determined by digital image analysis of tissue sections. Twenty‐four out of 30 adenomas could be unambiguously classified as high risk ( n = 9) or low risk ( n = 15) of progressing to cancer, based on DNA copy number profiles. Biological processes more prevalent in high‐risk than low‐risk adenomas were related to proliferation, tumor microenvironment and Notch, Wnt, PI3K/AKT/mTOR and Hedgehog signaling, while metabolic processes and protein secretion were enriched in low‐risk adenomas. DNA copy number driven gene‐dosage effect in high‐risk adenomas and cancers was observed for POFUT1, RPRD1B and EIF6 . Increased POFUT1 expression in high‐risk adenomas was validated in tissue samples and organoids. High POFUT1 expression was also associated with Notch signaling enrichment and with decreased goblet cells differentiation. In‐depth molecular characterization of colorectal adenomas revealed POFUT1 and Notch signaling as potential drivers of tumor progression. Abstract : What's new? Removal of colorectal adenomas is an effective strategy to reduce colorectal cancer (CRC) mortality rates. However, as only a minority of adenomas progress to cancer, such strategies may lead to overtreatment. While high‐risk adenomas, defined by specific DNA copy number aberrations, have an increased risk of progression, the mechanisms underlying colorectal adenoma‐to‐carcinoma progression remain unclear. This molecular characterization of colorectal adenomas, CRCs, and normal adjacent colon samples demonstrates that biological processes inherent to CRC are already more active in high‐risk adenomas compared to low‐risk adenomas. Moreover, the findings highlight POFUT1 and Notch signaling as potential drivers of colorectal tumor development.